Muscle activity between dentate and edentulous patients rehabilitated with dental prostheses: A systematic review - Neves, Bruna Rocha; Costa, Rayanna Thayse Florêncio; Vasconcelos, Belmiro Cavalcanti do Egito; Pellizzer, Eduardo Piza [UNESP]; Moraes, Sandra Lúcia Dantas (Wiley, 2023)
Background: Adequate muscle activity is important for the success of oral rehabilitation: it maintains the integrity of the stomatognathic system and is responsible for chewing movements needed to break, crush and grind food. Objective: To compare muscle activity using electromyography (EMG) while clenching or chewing soft and/or hard foods among individuals with natural dentition (ND) and edentulous patients rehabilitated with dental prostheses. Methods: This review was conducted until March, 2023, and the research question was “Is the muscle activity of edentulous patients rehabilitated with dental prostheses similar to that of dentate individuals?” A search strategy was conducted in PubMed/MEDLINE, The Cochrane Library, Web of Science, Lilacs, Embase and manual journal searches. Results: Ten studies were included in the analysis. Most of them reported that individuals with ND had significant higher muscle activity (clenching or chewing) than complete dentures (CD) users. However, no difference was observed between patients with full mouth implant-supported fixed dental prosthesis (ISFDP) and ND. Additionally, two studies compared patients with mandibular ISFDP with maxillary CD and individuals with ND and found no differences; however, one study concluded that patients with ISFDP with CD (maxillary or mandibular) had lower muscle activity than individuals with ND. Only one study reported a higher muscle activity in patients with full-mouth ISFDP than in individuals with ND. Conclusions: Bimaxillary CD users had lower muscle activity than individuals with ND. During rehabilitation, the muscle activity of patients with full-mouth ISFDP and mandibular ISFDP with maxillary CD is similar to individuals with ND.
Keywords: complete denture; dental implants; dental prosthesis; electromyography; masticatory muscles; systematic review